(untitled) (Al-Aasar, 2026)
This research paper examines China’s Belt and Road Initiative (BRI) as a key component of its soft power strategy, analyzing its implications for regional dynamics in Southeast Asia and beyond. China’s Belt and Road Initiative (BRI) has emerged as a pivotal component of its soft power diplomacy, aiming to enhance economic cooperation, cultural exchange, and strategic influence across participating nations. This paper assesses the BRI’s impact on regional dynamics, focusing on Southeast Asia, where China’s economic investments and infrastructure development have reshaped regional perceptions and alliances. Through a mix of qualitative analysis and case studies, this research evaluates how China’s BRI has influenced regional power structures, economic dependencies, and diplomatic alignments. The study reveals that while the BRI has bolstered China’s soft power and strategic influence, it has also raised concerns about debt sustainability, sovereignty, and regional competition. The paper concludes by elaborating on the intricate nature of China’s Belt and Road Initiative (BRI) and its associated soft power strategy. It emphasizes the multifaceted implications this strategy has for regional stakeholders, taking into account the diverse political, economic, and cultural dimensions at play. Additionally, the paper proposes thoughtful policy considerations to effectively navigate the challenges and opportunities presented by China’s expanding influence in the region.